Multi-metal catalyst synthesized by utilizing ion exchange as well as preparation method and application of multi-metal catalyst
Synthesis of CoAlPt polymetallic catalysts on hydrotalcite support by ion exchange method has solved the problem of low activity and selectivity of existing catalysts, and achieved efficient, stable and low energy consumption CO2 hydrogenation reaction, which has industrial application potential.
Patent Information
- Application Number
- CN202411578750.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
AI Technical Summary
The existing CO2 hydrogenation catalysts have problems such as low activity and selectivity, poor stability, and harsh reaction conditions, which leads to low product yield and high energy consumption, making it difficult to achieve industrial application.
The CoAlPt polymetallic catalyst is synthesized on a hydrotalcite support by ion exchange method. By adjusting the molar ratio of metal components and ion exchange conditions, the effective dispersion and synergistic effect of the Co, Al and Pt components are achieved.
It improves the activity, selectivity and stability of the catalyst, achieves high CO2 conversion and low carbon alcohol yield, reduces energy consumption, simplifies the preparation process, and is suitable for industrial applications.
Smart Images

Figure BDA0005122483500000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of CO2 hydrogenation synthesis of low-carbon alcohols (C1-C5), and specifically relates to a multi-metal catalyst synthesized by ion exchange and a preparation method and application thereof. Background Art
[0002] In today's world, global warming and fossil fuel depletion have become urgent issues that need to be resolved. The increasing concentration of carbon dioxide (CO2) in the atmosphere is one of the main causes of the greenhouse effect. In order to meet this challenge, converting CO2 into high-value-added chemicals and clean fuels is considered to be a promising strategy. CO2 hydrogenation technology has attracted widespread attention from researchers and the industry due to its unique advantages in reducing greenhouse gas emissions, achieving carbon recycling, producing clean fuels and synthesizing high-value-added chemicals. This technology can not only convert CO2 in the atmosphere or in industrial waste gas into useful products and reduce CO2 emissions, but also convert intermittent renewable energy (such as wind and solar energy) into chemical energy storage and improve energy efficiency.
[0003] However, despite the many advantages of CO2 hydrogenation technology, it still faces some challenges in practical applications. At present, the catalysts used in CO2 hydrogenation reactions generally have problems such as low activity and selectivity, poor stability, and harsh reaction conditions, resulting in low product yields and high energy consumption, making it difficult to achieve industrial application. Therefore, the development of efficient, stable, and economical CO2 hydrogenation catalyst systems is a key research direction in this field.
[0004] In recent years, multimetallic composite catalysts have attracted much attention due to their unique synergistic effects and excellent catalytic performance. The activity, selectivity and stability of the catalyst can be significantly improved by rationally designing the multimetallic components and their ratios. Among them, transition metals copper (Co), aluminum (Al) and precious metal platinum (Pt) are considered to be ideal components for constructing efficient CO2 hydrogenation catalysts. Co has good hydrogenation activity, Al can provide suitable acidic sites, and Pt helps to improve the stability and anti-poisoning ability of the catalyst.
[0005] The technical problems of the existing technology for preparing multi-metal composite catalysts mainly include: low precious metal loading, difficulty in introducing additives, high-temperature calcination leading to metal agglomeration, complex process and harsh reaction conditions, difficulty in separating and purifying products, uneven metal distribution that easily leads to atomic aggregation and inability to form single-atom catalysts, and environmentally unfriendly preparation process, large amount of waste liquid generated and complex post-treatment. These problems limit the activity and selectivity of the catalyst, affect the yield and energy consumption of the product, and make industrial application difficult to achieve. Summary of the invention
[0006] The present invention aims at the problems existing in the existing CO2 hydrogenation catalyst and proposes a novel multi-metallic CoAlPt composite hydrotalcite catalyst. The catalyst realizes the effective dispersion and synergistic effect of Co, Al and Pt components through the layered plate structure and unique composition of hydrotalcite, and exhibits excellent catalytic performance in the CO2 hydrogenation reaction to produce low-carbon alcohols (C1-C5), with high CO2 conversion rate and low-carbon alcohol yield. The prepared catalyst has the characteristics of large specific surface area and developed pore structure. Compared with the traditional method, it has the advantages of high catalytic efficiency, good stability and simple preparation process, and achieves higher product yield and lower energy consumption. It is expected to provide a new solution for the industrial application of CO2 hydrogenation technology and contribute to alleviating global warming and achieving sustainable development.
[0007] The technical scheme of the present invention is as follows:
[0008] A multi-metal catalyst synthesized by ion exchange, wherein the catalyst is composited by CoAlPt hydrotalcite and metal salt by ion exchange, the mass ratio of the CoAlPt hydrotalcite to the metal salt is 1-2:1-2, the CoAlPt hydrotalcite is composed of three metal elements Co, Al and Pt, and the molar ratio of each component is Co:Al:Pt=30-60:10-20:5-20.
[0009] Preferably, the metal salt is one or more of a metal acid salt and an organic acid salt.
[0010] Preferably, the metal loading of the catalyst is 14-24% and the specific surface area is 80-100m 2 / g, pore volume is 0.29-0.33cm 3 / g, and the average pore size is 5-7nm.
[0011] The catalyst is Mo-Cr-CoAlPt or Mn-W-CoAlPt.
[0012] A method for preparing the above-mentioned multi-metal catalyst, the method comprising the following steps:
[0013] (1) Preparation of mixed solution:
[0014] (1.1) Adding CoAlPt hydrotalcite into solvent A to prepare a solution A with a total mass concentration of 10-20%;
[0015] (1.2) adding a metal acid salt to solvent B to prepare a solution B with a total mass concentration of 5-20%;
[0016] (1.3) adding an organic acid salt to solvent C to prepare a solution C with a total mass concentration of 2-10%;
[0017] (1.4) Slowly add solution B to solution A under stirring and stir for 10-60 minutes to obtain a mixed solution D;
[0018] (1.5) Under stirring conditions, slowly add solution C to mixed solution D, and continue stirring for 10-60 minutes to obtain mixed solution E;
[0019] (1.6) adjusting the pH value of the obtained mixed solution E to 6-8, and ensuring that the change in the mass of the solvent does not exceed 10% of the total mass of the solvent;
[0020] (2) Ion exchange reaction:
[0021] (2.1) Add the pH-adjusted mixed solution E to the reaction kettle, add a mixed solvent consisting of two or more solvents at a rate of 1-5 mL / min under a protective atmosphere, control the temperature at 45-65° C., and stir at a speed of 300-600 rpm;
[0022] (2.2) After stirring the reaction system in the reactor for 24-72 hours, centrifugation is performed, and washing is performed 2-5 times with a mixed solvent comprising deionized water, alcohol and ketone;
[0023] (3) Drying and post-treatment:
[0024] (3.1) drying the solid after centrifugation at 70-90° C. and a vacuum degree of -0.05 to -0.2 MPa for 6-24 hours;
[0025] (3.2) Grind the dried sample to obtain a multi-metal catalyst.
[0026] Preferably, the metal acid salt is selected from one or more of chromate, manganate, molybdate, and tungstate, the organic acid salt is selected from one or more of acetate, citrate, oxalate, and formates, and the mass ratio of the sum of the mass of the metal acid salt and the organic acid salt to the mass of CoAlPt hydrotalcite is 1-2:1-2, wherein the mass ratio between the metal acid salt and the organic acid salt is 1:2 to 2.5:1.
[0027] Preferably, in step (1), solvent A, solvent B and solvent C are independently selected from a mixed solvent composed of one or more of alcohol, ketone, ether or amide and water in a volume ratio of 1:1-5.
[0028] Preferably, the reactor in step (2) is a high-pressure reactor, and the protective atmosphere is nitrogen, hydrogen, carbon dioxide or argon.
[0029] A use of the multi-metal catalyst in a carbon dioxide hydrogenation reaction.
[0030] Compared with the prior art, the present invention has the following optimization effects:
[0031] (1) The present invention uses CoAlPt hydrotalcite as a precursor, and can introduce a variety of transition metal additives under mild conditions through an ion exchange method, thereby overcoming the problems of low precious metal loading and difficulty in introducing additives; the prepared multi-metal catalyst has highly dispersed Pt, and the metal additives and Pt form a synergistic effect, thereby having high low-temperature catalytic activity and selectivity;
[0032] (2) The ion exchange method used in the present invention has a simple process, mild reaction conditions, easy product separation and purification, and avoids metal agglomeration caused by high-temperature calcination. In addition, the ion exchange method can evenly distribute metal ions on the surface of the carrier, avoid the aggregation of metal atoms, and help form a single-atom catalyst.
[0033] (3) The preparation process of the present invention is green and environmentally friendly, adopts a mixed solvent system of water phase and organic phase, generates less waste liquid, and is simple to post-process. DETAILED DESCRIPTION
[0034] Example 1
[0035] This embodiment adopts the following steps to prepare the multi-metal catalyst:
[0036] (1) Preparation of mixed solution:
[0037] (1.1) A certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) are dissolved in deionized water respectively, so that they exist in the solution at a molar ratio of Co:Al:Pt=45:15:20. Then, the above solution is slowly added to a 0.1 mol / L sodium hydroxide (NaOH) solution under stirring through a peristaltic pump, and the pH of the solution is adjusted to 8.5 to promote the formation of a precipitate. The resulting precipitate is separated by filtration, washed with deionized water for multiple times to remove impurities in the solution, and then the filter cake is dried at 80°C to obtain the desired CoAlPt hydrotalcite product;
[0038] (1.2) Add 1.0 g of CoAlPt hydrotalcite into 6.67 mL of deionized water to prepare a solution A with a total mass concentration of 15%;
[0039] (1.3) Add 0.28 g of sodium molybdate to 2.78 mL of a 1:1 mixed solution of DMSO and water to prepare a solution B with a total mass concentration of 10%;
[0040] (1.4) Add 0.17 g of sodium chromate to 3.33 mL of a 1:3 methanol:water mixture to prepare a solution C with a total mass concentration of 5%;
[0041] (1.5) While stirring, slowly add solution B to solution A and stir for 30 minutes to obtain a mixed solution D;
[0042] (1.6) While stirring, slowly add solution C to mixed solution D and continue stirring for 30 minutes to obtain mixed solution E;
[0043] (1.7) adjusting the pH value of the mixed solution E obtained in step (15) to 7 using 1 mol / L NaOH solution;
[0044] (2) Ion exchange reaction:
[0045] (2.1) Add the pH-adjusted mixed solution E into a 25 mL reactor. Under N2 protection, add a mixed solvent consisting of 3.33 mL of water, 1.33 mL of DMSO, and 1.67 mL of methanol at a rate of 3 mL / min. The temperature is controlled at 55 °C and stirred at 450 rpm.
[0046] (2.2) After stirring the reaction system in the reactor for 24 hours, the reaction system was centrifuged and washed four times with a mixed solvent consisting of 2.78 mL of deionized water, 2.78 mL of ethanol, and 2.78 mL of acetone;
[0047] (3) Drying and post-treatment:
[0048] (3.1) Drying the solid after centrifugation at 80°C and a vacuum degree of -0.09 MPa for 10 hours;
[0049] (3.2) The dried sample was ground to obtain 0.87 g of Mo-Cr-CoAlPt multi-metallic catalyst.
[0050] (4) Catalytic reaction test:
[0051] (4.1) The prepared metal catalyst was placed in a muffle furnace and calcined at 400 °C for 2 h;
[0052] (4.2) The calcined metal catalyst was transferred to a tube furnace and reduced at 300°C in a pure hydrogen atmosphere for 3 h;
[0053] (4.3) Take out the reduced metal catalyst from the tube furnace, weigh 0.5 g and place it in a high pressure reactor. In a mixed gas atmosphere of CO2:H2=1:1, the total pressure is 4 MPa, and the reaction is carried out at 180°C for 1 hour.
[0054] (4.4) After the reaction is completed, sample the reaction product and test and evaluate the activity and selectivity of the catalyst.
[0055] Example 2
[0056] This embodiment adopts the following steps to prepare the multi-metal catalyst:
[0057] (1) Preparation of mixed solution:
[0058] (1.1) A certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) are dissolved in deionized water respectively, so that they exist in the solution at a molar ratio of Co:Al:Pt=33:11:11. Then, the above solution is slowly added to a 0.1 mol / L sodium hydroxide (NaOH) solution under stirring through a peristaltic pump, and the pH of the solution is adjusted to 8.5 to promote the formation of a precipitate. The resulting precipitate is separated by filtration, washed with deionized water for multiple times to remove impurities in the solution, and then the filter cake is dried at 80°C to obtain the desired CoAlPt hydrotalcite product;
[0059] (1.2) Add 1.0 g of CoAlPt hydrotalcite into 8.33 mL of a mixed solution of DMSO:H2O=1:3 to prepare a solution A with a total mass concentration of 12%;
[0060] (1.3) Add 0.55 g of sodium manganate to 3.64 mL of water to prepare a solution B with a total mass concentration of 15%;
[0061] (1.4) Add 0.27 g of sodium formate to 5.45 mL of a 1:1 methanol:water mixture to prepare a solution C with a total mass concentration of 5%;
[0062] (1.5) Add 0.55 g of sodium tungstate to 5.45 mL of a mixed solution of ethylene glycol and water = 1:5 to prepare a solution D with a total mass concentration of 10%;
[0063] (1.6) Under ultrasonic conditions, solution B and solution C were added to solution A simultaneously, and ultrasonicated for 30 minutes to obtain a mixed solution E;
[0064] (1.7) While stirring, slowly add solution D to mixed solution E and continue stirring for 1 hour to obtain mixed solution F;
[0065] (1.8) adjusting the pH value of the mixed solution F obtained in step (16) to 6 using 1 mol / L citric acid solution;
[0066] (2) Ion exchange reaction:
[0067] (2.1) Add the pH-adjusted mixed solution F into a 50 mL reactor. Under CO2 protection, add a mixed solvent consisting of 6.82 mL ethylene glycol and 4.55 mL water at a rate of 4 mL / min. The temperature is controlled at 60 °C and stirred at 500 rpm.
[0068] (2.2) After stirring the reaction system in the reactor for 72 hours, the reaction system was centrifuged and washed three times with 15.15 mL of ethanol, 15.15 mL of deionized water, and 15.15 mL of acetone;
[0069] (3) Drying and post-treatment:
[0070] (3.1) Drying the solid after centrifugation at 75°C and a vacuum degree of -0.08 MPa for 8 hours;
[0071] (3.2) The dried sample was ground to obtain 1.47 g of Mn-W-CoAlPt multi-metal catalyst.
[0072] (4) Catalytic reaction test:
[0073] (4.1) The prepared metal catalyst was placed in a muffle furnace and calcined at 400 °C for 2 h;
[0074] (4.2) The calcined metal catalyst was transferred to a tube furnace and reduced at 300°C in a pure hydrogen atmosphere for 3 h;
[0075] (4.3) Take out the reduced metal catalyst from the tube furnace, weigh 0.5 g and place it in a high pressure reactor. In a mixed gas atmosphere of CO2:H2=1:3, the total pressure is 5 MPa, and the reaction is carried out at 200°C for 1 hour.
[0076] (4.4) After the reaction is completed, sample the reaction product and test and evaluate the activity and selectivity of the catalyst.
[0077] Example 3
[0078] This embodiment adopts the following steps to prepare the multi-metal catalyst:
[0079] (1) Preparation of mixed solution:
[0080] (1.1) A certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) are dissolved in deionized water respectively, so that they exist in the solution at a molar ratio of Co:Al:Pt=30:10:10. Then, the above solution is slowly added to a 0.1 mol / L sodium hydroxide (NaOH) solution under stirring through a peristaltic pump, and the pH of the solution is adjusted to 8.5 to promote the formation of a precipitate. The resulting precipitate is separated by filtration, washed with deionized water for multiple times to remove impurities in the solution, and then the filter cake is dried at 80°C to obtain the desired CoAlPt hydrotalcite product;
[0081] (1.2) Add 1.0 g of CoAlPt hydrotalcite to 10 mL of ethylene glycol: water = 1:2 to prepare a solution A with a total mass concentration of 10%;
[0082] (1.3) Add 0.8 g of sodium molybdate to 6.67 mL of DMSO: water = 1:5 to prepare a solution B with a total mass concentration of 12%;
[0083] (1.4) Add 0.2 g of sodium acetate to 10 mL of methanol: water = 1:1 to prepare a solution C with a total mass concentration of 2%;
[0084] (1.5) Add 1.0 g of sodium oxalate to 6.67 mL of ethylene glycol: water = 1:3 to prepare a solution D with a total mass concentration of 15%;
[0085] (1.6) Under reflux conditions, solution B, solution C and solution D are added to solution A in sequence, with an interval of 30 minutes between each addition. The mixture is refluxed for 2 hours to obtain a mixed solution E.
[0086] (1.7) adjusting the pH value of the mixed solution E obtained in step (15) to 8 using 1 mol / L ammonia solution;
[0087] (2) Ion exchange reaction:
[0088] (2.1) Add the pH-adjusted mixed solution E into a 100 mL reactor. Under Ar protection, add a mixed solvent consisting of 13.33 mL of ethylene glycol and 20 mL of deionized water at a rate of 2 mL / min. The temperature is controlled at 50 °C and stirred at 400 rpm.
[0089] (2.2) After the reaction system was stirred in the reactor for 53 hours, it was filtered and washed five times with a mixed solvent consisting of 8.33 mL of ethylene glycol, 16.67 mL of deionized water, and 16.67 mL of anhydrous ethanol;
[0090] (3) Drying and post-treatment:
[0091] (3.1) Dry the filtered solid at 70°C and a vacuum degree of -0.1 MPa for 12 hours;
[0092] (3.2) The dried sample was ground to obtain 1.82 g of Mo-CoAlPt multi-metallic catalyst.
[0093] (4) Catalytic reaction test:
[0094] (4.1) The prepared metal catalyst was placed in a muffle furnace and calcined at 400 °C for 2 h;
[0095] (4.2) The calcined metal catalyst was transferred to a tube furnace and reduced at 300°C in a pure hydrogen atmosphere for 3 h;
[0096] (4.3) Take out the reduced metal catalyst from the tube furnace, weigh 0.5 g and place it in a high pressure reactor. In a mixed gas atmosphere of CO2:H2=1:2, the total pressure is 5 MPa, and the reaction is carried out at 160°C for 1 hour.
[0097] (4.4) After the reaction is completed, sample the reaction product and test and evaluate the activity and selectivity of the catalyst.
[0098] Example 4
[0099] This embodiment adopts the following steps to prepare the multi-metal catalyst:
[0100] (1) Preparation of mixed solution:
[0101] (1.1) A certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) are dissolved in deionized water respectively, so that they exist in the solution at a molar ratio of Co:Al:Pt=27:9:9:25:20:10. Then, the above solution is slowly added to a 0.1 mol / L sodium hydroxide (NaOH) solution under stirring through a peristaltic pump, and the pH of the solution is adjusted to 8.5 to promote the formation of a precipitate. The resulting precipitate is separated by filtration, washed with deionized water several times to remove impurities in the solution, and then the filter cake is dried at 80°C to obtain the desired CoAlPt hydrotalcite product;
[0102] (1.2) Add 1.0 g of CoAlPt hydrotalcite to 6.67 mL of ethylene glycol: water = 1:2 to prepare a solution A with a total mass concentration of 15%;
[0103] (1.3) Add 0.63 g of sodium chromate to 5.15 mL of DMSO: water = 1:5 to prepare a solution B with a total mass concentration of 18%;
[0104] (1.4) Add 0.74 g of sodium manganate to 6.18 mL of water to prepare a solution C with a total mass concentration of 12%;
[0105] (1.5) Add 0.37 g of sodium citrate to 7.41 mL of N,N-dimethylformamide: water = 1:3 to prepare a solution D with a total mass concentration of 5%;
[0106] (1.6) Under nitrogen protection and ultrasonic conditions, solution B and solution D were added to solution A at the same time, and ultrasonicated for 1 hour to obtain a mixed solution E;
[0107] (1.7) While stirring, slowly add solution C dropwise to mixed solution E and continue stirring for 2 hours to obtain mixed solution F;
[0108] (1.8) adjusting the pH value of the mixed solution F obtained in step (16) to 7 using a buffer solution consisting of 0.1 mol / L citric acid and 0.2 mol / L phosphoric acid;
[0109] (2) Ion exchange reaction:
[0110] (2.1) Add the pH-adjusted mixed solution F into a 200 mL reactor. Under H2 protection, add a mixed solvent consisting of 4.63 mL ethylene glycol, 13.89 mL water, and 4.63 mL DMSO at a rate of 5 mL / min. The temperature is controlled at 65 °C and stirred at 550 rpm.
[0111] (2.2) After the reaction system was stirred in the reactor for 48 hours, it was filtered and washed four times with a mixed solvent consisting of 18.52 mL of N,N-dimethylformamide, 18.52 mL of ethanol, and 55.56 mL of deionized water;
[0112] (3) Drying and post-treatment:
[0113] (3.1) Dry the filtered solid at 85°C and a vacuum degree of -0.095 MPa for 6 hours;
[0114] (3.2) The dried sample was ground to obtain 2.19 g of Cr-Mn-CoAlPt multi-metallic catalyst.
[0115] (4) Catalytic reaction test:
[0116] (4.1) The prepared metal catalyst was placed in a muffle furnace and calcined at 400 °C for 2 h;
[0117] (4.2) The calcined metal catalyst was transferred to a tube furnace and reduced at 300°C in a pure hydrogen atmosphere for 3 h;
[0118] (4.3) Take out the reduced metal catalyst from the tube furnace, weigh 0.5 g and place it in a high pressure reactor. In a mixed gas atmosphere of CO2:H2=1:1, the total pressure is 5 MPa, and the reaction is carried out at 140°C for 1 hour.
[0119] (4.4) After the reaction is completed, sample the reaction product and test and evaluate the activity and selectivity of the catalyst.
[0120] Comparative Example 1
[0121] This comparative example uses a coprecipitation method to synthesize a multi-metal catalyst, the catalyst is composed of Co, Al, and Pt elements, and the molar ratio of Co, Al, and Pt is 45:15:1. The preparation method comprises the following steps:
[0122] (1) Co(NO3)2·6H2O, Al(NO3)3·9H2O and H2PtC l6 6H2O, dissolved in deionized water at a molar ratio of Co:Al:Pt:=45:15:1, to prepare a mixed solution with a total mass concentration of 15%;
[0123] (2) under stirring conditions, the mixed solution obtained in step (1) was added dropwise into an NH3·H2O solution with a pH value of 8 to generate a precipitate, and stirring was continued for 30 minutes;
[0124] (3) The precipitate obtained in step (2) is filtered, washed with deionized water until neutral, dried at 80° C. for 12 hours, calcined at 450° C. for 4 hours, and ground to obtain a CoAlPt multi-metal catalyst.
[0125] (4) Catalytic reaction test:
[0126] (4.1) The calcined metal catalyst was transferred to a tube furnace and reduced in a pure hydrogen atmosphere at 300°C for 3 h;
[0127] (4.2) Take out the reduced metal catalyst from the tube furnace, weigh 0.5 g and place it in a high pressure reactor. In a mixed gas atmosphere of CO2:H2=1:1, the total pressure is 4 MPa, and the reaction is carried out at 180°C for 1 hour.
[0128] (4.3) After the reaction is completed, sample the reaction product and test and evaluate the activity and selectivity of the catalyst.
[0129] Comparative Example 2
[0130] (1) Preparation of mixed solution:
[0131] (1.1) A certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), aluminum nitrate nonahydrate (Al(NO3)3·9H2O) and chloroplatinic acid hexahydrate (H2PtCl6·6H2O) are dissolved in deionized water respectively, so that they exist in the solution at a molar ratio of Co:Al:Pt=27:9:9:25:20:10. Then, the above solution is slowly added to a 0.1 mol / L sodium hydroxide (NaOH) solution under stirring through a peristaltic pump, and the pH of the solution is adjusted to 8.5 to promote the formation of a precipitate. The resulting precipitate is separated by filtration, washed with deionized water several times to remove impurities in the solution, and then the filter cake is dried at 80°C to obtain the desired CoAlPt hydrotalcite product;
[0132] (1.2) Add 1.0 g of CoAlPt hydrotalcite to 6.67 mL of ethylene glycol: water = 1:2 to prepare a solution A with a total mass concentration of 15%;
[0133] (1.3) Add 0.63 g of sodium chromate to 5.15 mL of DMSO: water = 1:5 to prepare a solution B with a total mass concentration of 18%;
[0134] (1.4) Add 0.37 g of sodium citrate to 7.41 mL of N,N-dimethylformamide: water = 1:3 to prepare a solution C with a total mass concentration of 5%;
[0135] (1.5) Under nitrogen protection and ultrasonic conditions, solution B and solution C were added to solution A at the same time, and ultrasonicated for 1 hour to obtain a mixed solution D;
[0136] (1.6) Under stirring conditions, slowly add solution B dropwise to mixed solution D and continue stirring for 2 hours to obtain mixed solution E;
[0137] (1.7) adjusting the pH value of the mixed solution E obtained in step (16) to 7 using a buffer solution consisting of 0.1 mol / L citric acid and 0.2 mol / L phosphoric acid;
[0138] (2) Ion exchange reaction:
[0139] (2.1) Add the pH-adjusted mixed solution E into a 200 mL reactor. Under H2 protection, add a mixed solvent consisting of 4.63 mL ethylene glycol, 13.89 mL water, and 4.63 mL DMSO at a rate of 5 mL / min. The temperature is controlled at 65 °C and stirred at 550 rpm.
[0140] (2.2) After the reaction system was stirred in the reactor for 48 hours, it was filtered and washed four times with a mixed solvent consisting of 18.52 mL of N,N-dimethylformamide, 18.52 mL of ethanol, and 55.56 mL of deionized water;
[0141] (3) Drying and post-treatment:
[0142] (3.1) Dry the filtered solid at 85°C and a vacuum degree of -0.095 MPa for 6 hours;
[0143] (3.2) Grind the dried sample to obtain 1.17 g of Cr-CoAlPt multi-metallic catalyst.
[0144] (4) Catalytic reaction test:
[0145] (4.1) The prepared metal catalyst was placed in a muffle furnace and calcined at 400 °C for 2 h;
[0146] (4.2) The calcined metal catalyst was transferred to a tube furnace and reduced at 300°C in a pure hydrogen atmosphere for 3 h;
[0147] (4.3) Take out the reduced metal catalyst from the tube furnace, weigh 0.5 g and place it in a high pressure reactor. In a mixed gas atmosphere of CO2:H2=1:1, the total pressure is 5 MPa, and the reaction is carried out at 140°C for 1 hour.
[0148] (4.4) After the reaction is completed, sample the reaction product and test and evaluate the activity and selectivity of the catalyst.
[0149] Table 1: Experimental data and results
[0150]
[0151] The present invention illustrates the technical concept of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of individual raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A multi-metal catalyst synthesized by ion exchange, characterized in that :The catalyst is composited by CoAlPt hydrotalcite and metal salt through ion exchange, the mass ratio of CoAlPt hydrotalcite to metal salt is 1-2:1-2, the CoAlPt hydrotalcite is composed of three metal elements Co, Al and Pt, and the molar ratio of each component is Co:Al:Pt=30-60:10-20:5-20.
2. The catalyst according to claim 1, characterized in that The metal salt is one or more of a metal acid radical salt and an organic acid radical salt.
3. The catalyst according to claim 1, characterized in that The metal loading of the catalyst is 14-24% and the specific surface area is 80-100m 2 / g, pore volume is 0.29-0.33cm 3 / g, and the average pore size is 5-7nm.
4. The catalyst according to claim 1, characterized in that The catalyst is Mo-Cr-CoAlPt or Mn-W-CoAlPt.
5. A method for preparing a multi-metal catalyst according to claim 1, characterized in that : The method comprises the following steps: (1) Preparation of mixed solution: (1.1) Adding CoAlPt hydrotalcite into solvent A to prepare a solution A with a total mass concentration of 10-20%; (1.2) adding a metal acid salt to solvent B to prepare a solution B with a total mass concentration of 5-20%; (1.3) adding an organic acid salt to solvent C to prepare a solution C with a total mass concentration of 2-10%; (1.4) Slowly add solution B to solution A under stirring and stir for 10-60 minutes to obtain a mixed solution D; (1.5) Under stirring conditions, slowly add solution C to mixed solution D, and continue stirring for 10-60 minutes to obtain mixed solution E; (1.6) adjusting the pH value of the obtained mixed solution E to 6-8, and ensuring that the change in the mass of the solvent does not exceed 10% of the total mass of the solvent; (2) Ion exchange reaction: (2.1) Add the pH-adjusted mixed solution E to the reaction kettle, add a mixed solvent consisting of two or more solvents at a rate of 1-5 mL / min under a protective atmosphere, control the temperature at 45-65° C., and stir at a speed of 300-600 rpm; (2.2) After stirring the reaction system in the reactor for 24-72 hours, centrifugation is performed, and washing is performed 2-5 times with a mixed solvent comprising deionized water, alcohol and ketone; (3) Drying and post-treatment: (3.1) drying the solid after centrifugation at 70-90° C. and a vacuum degree of -0.05 to -0.2 MPa for 6-24 hours; (3.2) Grind the dried sample to obtain a multi-metal catalyst.
6. The method according to claim 5, characterized in that : The metal acid salt is selected from one or more of chromate, manganate, molybdate, and tungstate, and the organic acid salt is selected from one or more of acetate, citrate, oxalate, and formates. The mass ratio of the sum of the mass of the metal acid salt and the organic acid salt to the mass of the CoAlPt hydrotalcite is 1-2:1-2, wherein the mass ratio between the metal acid salt and the organic acid salt is 1:2 to 2.5:
1.
7. The method according to claim 5, characterized in that In step (1), solvent A, solvent B and solvent C are independently selected from a mixed solvent composed of one or more of alcohol, ketone, ether or amide and water in a volume ratio of 1:1-5.
8. The method according to claim 5, characterized in that : The reactor in step (2) is a high-pressure reactor, and the protective atmosphere is nitrogen, hydrogen, carbon dioxide or argon.
9. Use of the multimetallic catalyst according to claim 1 in a carbon dioxide hydrogenation reaction.